Modelling insurgent-incumbent dynamics: vector autoregressions, multivariate Markov chains, and the nature of technological competition - Damásio, B.; Mendonça, S. (Applied Economics Letters, 2019)
The struggle between sail and steam is a long-standing theme in economic history. But this technological competition story has only been partly tackled, since most studies have appreciated the rivalry between the two alternative modes of commercial sea carriage in the late 19th century while the early period has remained relatively under-analysed. This paper models the early dynamics between the two capital goods using a vector autoregression approach (VAR) and a Multivariate Markov Chain approach (MMC). We find evidence that the relationship was non-linear, with a strong indication of complementarities and cross-technology learning effects.